Terminology and the evolution of linguistic prejudice: the conceptual domain of ‘Irishness’ in the Historical Thesaurus of English and the Hansard Corpus of British Parliamentary Speeches - John Blair Corbett (TradTerm, 2021)
This article draws on the Historical Thesaurus of English and related resources, the Mapping Metaphor project and the semantically tagged Hansard Corpus of British Parliamentary Speeches, to consider how the Irish have been imagined and named in Anglophone culture, and how ‘Irishness’, alongside the attributes of other ‘races and nations’, in the terminology of the Mapping Metaphor project, has developed metaphorically over time, with a focus on the association between Irishness and anger and foolishness. The article concludes by illustrating how the names and metaphors of the Irish are contested discursively in a corpus of British Parliamentary speeches. The article serves as a practical introduction to the Historical Thesaurus of English and the Hansard Corpus and how they may be used, in conjunction with related online resources, to explore aspects of English language, discourse and culture.